Uneven development and displaced care in Sri Lanka. (July 2018) - Withers, Matt; Piper, Nicola
Temporary labour migration has become a defining characteristic of Sri Lanka's economy. The concentration of production and services in and around urban Colombo has produced a lopsided pattern of development that undermines traditional rural livelihoods and necessitates practices of 'survival migration'. Such migration has been starkly gendered: export production has been explicitly feminised through the creation of garment factories operating in export processing zones, and through the displacement of care in the form of internal and international migrant domestic work. This article examines the displacement and commodification of care through the lens of domestic worker migration. It situates this at the intersection of gender, ethnicity and class, both geographically and historically, and analyses the Interrelationship between internal and international migration. This framework is then used to explore the changing dynamics of, and attitudes towards, domestic work. Migrant domestic work is explicitly bound up in uneven development, articulated through a continuum of gendered and ethnic subordination. There are many differentiated outcomes and experiences of constrained agency within this process.